Relative age effect and performance in elite youth male basketball - Tascioglu, R.; Atalag, O.; Yuksel, Y.; Kocaeksi, S.; Güven, G.; Akyildiz, Z.; Nobari, H. (Scientific Reports, 2023)
The aims of the study were to (i) assess the Relative Age Effect (RAE) on elite young male basketball players, (ii) to analyze whether there is a difference between birth quarters (BQ) according to their minutes played and efficiency ratings as individual performance parameters and, (iii) to analyze the relationship between team efficiency, team success, and RAE with a new approach. The research was conducted on 678 players (Age:15.84 ± 0.42) from 53 teams in six different tournaments (from 2014 to 2019). Although, chi-square test showed that more players were born in first BQ than in all other BQs (p < 0.05), no significant difference between BQs and performance measures was found (p > 0.05). However, a relationship between team RAE score, tournament ranking, and team efficiency score was found (p < 0.05). Furthermore, there was a relationship between tournament rankings and team RAE rankings (p < 0.05). While players born in the first months of the year were more likely to be selected for the national youth teams, performance parameters did not show any significant difference when compared to other players who were born later in the same year. However, results showed that teams that have a higher number of athletes who were born in the earlier months of a year showed higher achievement in the tournaments.